Cell wall and tannin treatments for increased utilisation of cassava and sorghum in beverage and bioethanol production - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2015.